Analisis Lingkungan Internal Dan Eksternal Studi Kasus: PT Intan Pariwara Klaten - Nurcahyani Dewi Retnowati (Jurnal Buana Informatika, 2010)
Abstract. Analysis of Internal and External Environment, Case Study: PT Intan Pariwara Klaten. The analysis of the Eksternal Environment covered the PEST Analysis (Politics, Ekonomi, Sosial and Technology) that included the condition for the macro Indonesian environment, that is the economy, technology, politics/the law, and sosiokultural. The analysis of the Eksternal Environment that was second was the model of competition pressures that explained about five threats, that is the competition from available competitors, competitors's new threat, the threat or substitution services of products, the strength bargained from customers, and the strength bargained from suppliers. The analysis of the Internal Environment used the Diagram of the Context that depicted relations between the system and the external side that were related to the company's business. Relations could be between the system and the external side that were related to PT Intan Pariwara depicted to the diagram of the context that explained that there is four related external sides, that is the Printing House, Writers and the Buyer that consisted of the Elementary School level student and the Senior High School and the public's community.  Keywords: Analysis of External Environment, Analysis of Internal Environment, Business Context Abstrak. Analisis Lingkungan Eksternal meliputi Analisis PEST  (Politik, Ekonomi, Sosial dan Teknologi) yang mencakup kondisi lingkungan makro Indonesia, yaitu perekonomian, teknologi, politik/hukum, dan sosiokultural. Analisis Lingkungan Eksternal yang kedua adalah model tekanan-tekanan kompetisi yang menjelaskan tentang lima ancaman, yaitu persaingan dari pesaing-pesaing yang sudah ada, ancaman pesaing-pesaing baru, ancaman produk-produk atau jasa-jasa substitusi, kekuatan menawar dari pelanggan-pelanggan, dan kekuatan menawar dari pemasok-pemasok. Analisis Lingkungan Internal menggunakan Diagram Konteks yang menggambarkan hubungan antara sistem dan pihak eksternal yang terkait dengan bisnis perusahaan.          Hubungan antara sistem dan pihak eksternal yang terkait dengan PT Intan Pariwara dapat digambarkan pada diagram konteks yang menjelaskan bahwa ada empat pihak eksternal yang terkait, yaitu Percetakan, Penulis, Perwakilan dan Pembeli yang terdiri dari siswa tingkat TK hingga SMA dan masyarakat umum. Kata Kunci: Analisis Lingkungan Eksternal, Analisis Lingkungan Internal, Konteks Bisnis